Eicosanoids in inflammation in the blood and the vessel - Yamaguchi, Adriana; Botta, Eliana; Holinstat, Michael (Frontiers in Pharmacology, 2022)
Polyunsaturated fatty acids (PUFAs) are structural components of membrane phospholipids in cells. PUFAs regulate cellular function through the formation of derived lipid mediators termed eicosanoids. The oxygenation of 20-carbon PUFAs via the oxygenases cyclooxygenases, lipoxygenases, or cytochrome P450, generates a class of classical eicosanoids including prostaglandins, thromboxanes and leukotrienes, and also the more recently identified hydroxy-, hydroperoxy-, epoxy- and oxo-eicosanoids, and the pro-resolving lipid mediators. These eicosanoids play a critical role in the regulation of inflammation in the blood and the vessel. While arachidonic acid-derived eicosanoids are extensively studied due to their pro-inflammatory effects and therefore involvement in the pathogenesis of inflammatory diseases such as atherosclerosis, diabetes mellitus, hypertension, and the coronavirus disease 2019; in the recent years, several eicosanoids have been reported to attenuate exacerbated inflammatory response and participate in the resolution of inflammation. This review focused on elucidating the biosynthesis and the mechanistic signaling of the eicosanoids in inflammation, as well as the pro-inflammatory and anti-inflammatory effects of these eicosanoids in the blood and the vascular wall.